Karakteristik Morfologi Mutan Cabai Hias Hasil Irradiasi Sinar Gamma - Zulfa Ulinnuha; Noor Farid; Imastini Dinuriah (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2023)
Chili is used not only as a vegetable for consumption or a complement to dishes but also as an attractive ornamental plant to cultivate. One of the genetic enhancement efforts is through mutation induction with gamma rays. The aim of this study was to increase the genetic diversity of ornamental chilies by inducing gamma ray mutations. This research was conducted at BATAN (National Nuclear Energy Agency), experimental field and Plant Breeding and Biotechnology Laboratory, Faculty of Agriculture, Jenderal Soedirman University. The research was conducted from July to November 2022. The results showed that the LD50 value of gamma-ray irradiated chili seeds was 213.49 Gy, and there was an increase in the diversity of ornamental chili mutants. The color characteristic of mature leaves was purplish-green in the control plant, while the mutant turned purple on the upper and lower surfaces of the leaves. The character of the flower has not changed; that is, it remains purple, and the flower stalk remains upright. The stem pigment in control plants was a purple-green line, changed to purple in mutants. Mutant plant habitus changed to compact. These characters increase the aesthetic value of the ornamental chili mutant.